Graphene Synthesis, Characterization, Properties and Applications - Ru Gong, Jian (IntechOpen, 2011)
The discovery of graphene has led to a deluge of international research interest, and this new material in the field of materials science and condensed-matter physics has revealed a cornucopia of new physics and potential applications. This collection gives a roughly review on the recent progress on the synthesis, characterization, properties and applications of graphene, providing useful information for researchers interested in this area.